Pharmacokinetic studies of a three-component complex that repurposes the front line antibiotic isoniazid against Mycobacterium tuberculosis. (December 2017) - Manning, Thomas J.; Wilkerson, Kyle; Holder, Taylor; Bartley, Andrew Carson; Jackson, Chelsea; Plummer, Sydney; Phillips, Dennis; Krajewski, Logan; Wylie, Greg
Abstract: The frontline tuberculosis (Tb) antibiotic isoniazid has been repurposed using a three component complex aimed at increasing the delivery efficiency and adding new avenues to its mechanism of action. This study focuses on pharmacokinetic studies of the isoniazid-sucrose–copper (II)-PEG-3350 complex. The assays include the Plasma Protein Binding Assay (85.8%), Caco-2 Permeability Assay (B→APapp, 0.13 × 10 −6  cm/s), Cytochrome P450 Inhibition Assay (i.e. CYP2B6, IC50  = 7.26 μM), In vitro microsomal Stability Assay (t1/2 NADPH-Dependent > 240 min), and HepG2 Cytotoxicity (no toxicity). The National Cancer Institute's 60 cell line panel is used to measure activity against cancer cells. The percent growth values averaged over all 60 cell lines indicates the complex has no anti-cancer activity, which also suggests a lack of general toxicity. It also provides data for the complexes specificity against Mycobacterium tuberculosis .